The Effect of Cloud Computing on Elements of Accounting Information System (Global Journal of Management and Business Research, 2017)
The Purpose of this paper is to identifying the impact of Cloud Computing on the Elements of the Accounting Information System represented by: Establishment "Accounting Entity.",
Keywords: cloud computing; accounting information system; elements of the accounting information system